PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO DAN TOTAL ASSET TURNOVER TERHADAP RETURN ON EQUITY PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX - Nurul Aini; Hamida Sari Siregar (Smart Education, 2026)
Abstract: This study aims to analyze the effect of Current Ratio, Debt to Equity Ratio, and Total Asset Turnover on Return on Equity both simultaneously and partially in companies listed on the Jakarta Islamic Index for the 2022-2024 period. The study population was 30 companies, with a sample of 18 companies selected using a purposive sampling method, resulting in 54 observations. The analysis method used was multiple linear regression. The results showed that simultaneously, Current Ratio, Debt to Equity Ratio, and Total Asset Turnover had a significant effect on Return on Equity with a calculated Fvalue (32,555) > Ftable (2,79) and a significance value of 0,000 < 0,05. Partially, Current Ratio did not have a significant effect on Return on Equity with a calculated tvalue of 0.249 < ttable 2,00758 and a significance value of 0,804 > 0,05. The Debt to Equity Ratio has a positive and significant effect, with a calculated tvalue of 5,510 > ttable 2,00758 and a significance value of 0,00 < 0,05. Total Asset Turnover has a positive and significant effect, with a calculated tvalue of 3,514 > ttable 2,00758 and a significance value of 0,01 < 0,05. The Adjusted R Square value of 0,641 indicates that 64,1% of the variation in Return on Equity can be explained by the Current Ratio, Debt to Equity Ratio, and Total Asset Turnover, while the remaining 35,9% is explained by other variables outside the research model. Keywords: Current Ratio, Debt to Equity Ratio, Total Asset Turnover, and Return on Equity Abstrak: Penelitian ini bertujuan untuk menganalisis pengaruh Current Ratio, Debt to Equity Ratio dan Total Asset Turnover terhadap Return on Equity baik secara simultan dan parsial pada perusahaan yang terdaftar di Jakarta Islamic Index periode 2022-2024. Populasi penelitian ini 30 perusahaan, dengan sampel sebanyak 18 perusahaan yang dipilih menggunakan metode purposive sampling, sehingga diperoleh 54 pengamatan. Metode analisis yang digunakan adalah regresi linear berganda. Hasil penelitian menunjukkan bahwa secara simultan Current Ratio, Debt to Equity Ratio dan Total Asset Turnover berpengaruh signifikan terhadap Return on Equity dengan nilai Fhitung (32,555) > Ftabel (2,79) dan nilai signifikansi 0,000 < 0,05. Secara parsial, Current Ratio tidak berpengaruh signifikan terhadap Return on Equity dengan nilai thitung 0,249 < ttabel 2,00758 dan nilai signifikansi 0,804 > 0,05. Debt to Equity Ratio berpengaruh positif dan signifikan dengan nilai thitung 5,510 > ttabel 2,00758 dan nilai signifikansi 0,00 < 0,05. Total Asset Turnover berpengaruh positif dan signifikan dengan nilai thitung 3,514 > ttabel 2,00758 dan nilai signifikansi 0,01 < 0,05. Nilai Adjusted R Square adalah 0,641 menunjukkan bahwa 64,1% variasi Return on Equity yang dapat dijelaskan oleh Current Ratio, Debt to Equity Ratio dan Total Asset Turnover sedangkan sisanya 35,9% dijelaskan oleh variabel lain diluar model penelitian. Kata Kunci: Current Ratio, Debt to Equity Ratio, Total Asset Turnover dan Return on Equity